The social democratic full-employment model in transition: The Scandinavian experiences in the 1980s and 1990s - Sven Jochem (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 1998)
The Social Democratic Full Employment Model in the Nordic Countries underwent a rapid transition in the 1980s and early 1990s. In this paper, change and continuity is examined along thre dimensions: the political stimulation of demand for labour, the political incentives influencing labour supply, and thirdly, the politics targeted towards enhancing the matching process on the labour market. In the first dimension it is shown that in all four countries the consensual wage bargaining systems were eroded in the 1980s which implied high wage increases and, as a consequence, shrinking employment. Despite the progress of globalisation, this institutional erosion was the main cause of the Nordic employment crisisin the early 1990s. In Denmark, Norway, and - not until the mid 1990s - Finland, the wage bargaining systems could be remodelled, but not so in Sweden. It is shown that this difference was caused by the reluctance of Swedish governments to release the employers fromthe financial burden of the welfare state. In the second dimension it is argued that the labour force supply declined in all four countries. The end of the Nordic 'Work Societies' can partly be explained by the strategic social policies of the various governments. In the third section, it is shown that the Social Democratic Model remained stable: In all four countries, active labour market policies are still at the centre of public attempts to improve the matching process on the labour market. Hence, continuity and change are mixed in the Nordic Full Employment Model. Taken together, this paper argues, that a restoration of the Social Democratic Full Employment Model in a world of globalised financial markets is based on a combination of moderate wage policies and a relieving of the employers of thecosts of the welfare state.
Keywords: 300